Panax notoginseng saponins alleviate skeletal muscle insulin resistance by regulating the IRS1–PI3K–AKT signaling pathway and GLUT4 expression. Issue 5 (26th April 2019) - Guo, Xuan; Sun, Wen; Luo, Guangbin; Wu, Lili; Xu, Guangyuan; Hou, Dan; Hou, Yi; Guo, Xiangyu; Mu, Xiaohong; Qin, Lingling; Liu, Tonghua
Abstract : Panax notoginseng saponins (PNS) are a commonly used traditional medicine to treat diabetes in China. Recent studies have confirmed their anti‐diabetic effects, but the underlying mechanisms have remained unclear. The present study was designed to explore whether PNS decrease hyperglycemia by improving insulin sensitivity in skeletal muscle and to elucidate the molecular mechanisms. The anti‐diabetic effects of PNS were analyzed in a skeletal myoblast cell line, C2C12, and in high fat diet‐induced diabetic KKAy mice. C2C12 cells were treated with PNS (50, 100, and 200 μg·L −1 ) and examined for glucose uptake, cell viability and expression of components of the phosphoinositide 3‐kinase (PI3K)–protein kinase B (AKT) signaling pathway. KKAy mice were intraperitoneally injected with PNS (200 mg·kg −1 ) for 6 weeks. Body weight, blood glucose, serum insulin, serum lipid, glucose and insulin tolerance were measured to evaluate the anti‐diabetic effects of PNS. Pathological changes, apoptosis and the PI3K–AKT signaling pathway were analyzed in KKAy skeletal muscle. PNS significantly increased insulin‐induced glucose uptake, but did not affect the cell viability of C2C12 cells. In addition, PNS reduced blood glucose and serum insulin levels and improved glucose tolerance and insulin tolerance of KKAy mice. Pathological changes and apoptosis of skeletal muscle were relieved by PNS treatment. Moreover, PNS treatment enhanced expression of mRNA encoding IRS1 and GLUT4, as well as the protein expression of phosphorylated (p) ‐insulin receptor substrate 1 (IRS1), p‐PI3K, p‐AKT and glucose transporter type 4 (GLUT4) in C2C12 and KKAy mouse muscle. Collectively, these data indicate that PNS reduces hyperglycemia and insulin resistance through up‐regulating GLUT4 expression and the IRS1–PI3K–AKT signaling pathway. Furthermore, PNS alleviated diabetes skeletal muscle pathological damage. Thus, our data suggest that PNS may be promising anti‐diabetic compounds. Abstract : Panax notoginseng saponins (PNS) are the major anti‐diabetic component of Panax notoginseng and commonly used to treat diabetes. We evaluated the anti‐diabetic benefits of PNS in KKay mice and C2C12 cells. PNS possess anti‐diabetic properties that improve glucose metabolism and insulin resistance, and rescue pathological injury through activating IRS1–PI3K–AKT signaling and up‐regulating GLUT4 expression in skeleton muscle cells.